2017
DOI: 10.1186/s12879-017-2750-9
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin resistance in mycobacterium tuberculosis patients using GeneXpert at Livingstone Central Hospital for the year 2015: a cross sectional explorative study

Abstract: BackgroundSince the recent introduction of GeneXepert for the detection of Tuberculosis (TB) drug resistance mutations in both primary resistance and acquired resistance in Zambia, little has been documented in literature on the issue of rifampicin resistance especially in the face of a high National TB burden. The study aimed to determine the prevalence of rifampicin resistance in tuberculosis patients at Livingstone Central Hospital for the year 2015.MethodsThis was a cross sectional study conducted at Livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
21
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 15 publications
11
21
8
Order By: Relevance
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 83%
“…According to our study, we found 132 (9.1%) of rifampicin-resistant cases among con rmed TB cases. This result is comparable with studies conducted in Debre Markos Referral Hospital (10.3%) [13], Felege Hiwot Referral Hospital and Debre Tabor Hospital (9.3%) [20], Addis Ababa (9.9 %) [48] and India (10.5%) [38].Our nds are higher than studies conducted on northwest, east and south parts of Ethiopia (2.9%-5.7%) [6,19,31-32,39,42,46 and 48], Nigeria (2.9%) [24] and Zambia (5.9%) [33].The possible explanation for these variations could be related to our retrospective approach spanning four years, or differences in study designs .However, our incidence was lower than for studies conducted in Gondar 15.8% [14],other parts of Ethiopia (11.5-39.4) [39-40and 51],Congo (42.2%) [47] and China (17.6-26.3%) [43 and 50].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The positivity finding was in line with studies conducted in Gonder (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] & Agaro Teaching Health Center in southwestern Ethiopia [36]. There are however contrary findings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 81%
“…However, our findings were higher than studies conducted in the Debre Markos Referral Hospital (16.6%) [13], different studies across Ethiopia (20.3-24.2 %) [14,[29][30][31][32], and a WHO estimation for Ethiopia of 14% (9.6%-19%) [2]. Conversely, the findings were lower than studies conducted in the FelegeHiwot Referral Hospital and Debre Tabor Hospital (41.9%) [20], Zambia (98.3%) [33] & South Africa (>70%) [34]. The possible explanations for this difference could be reflect policy recommendations for which HIV infected patients, as an eligible group, are more likely to be tested using GeneXpert™.…”
Section: Discussionmentioning
confidence: 92%